Identity and redistribution - Erik Lindqvist; Robert Östling (Stockholm School of Economics, The Economic Research Institute (EFI), 2006)
This paper models the interaction between individuals' identity choices and redistribution. Both redistributive policies and identity choices are endogenous, and there might be multiple equilibria. The model is applied to ethnicity and social class. In an equilibrium with high taxes, the poor identify as poor and favor high taxes. In an equilibrium with low taxes, at least some of the poor identify with their ethnic group and favor low taxes. The model has two main predictions. First, redistribution is highest when society is ethnically homogenous, but the effect of ethnic diversity on redistribution is not necessarily monotonic. Second, when income inequality is low, an increase in income inequality might induce the poor to identify with their ethnic group and therefore favor lower taxes.
Keywords: H20; J15; 330; Redistribution; social identity; income inequality; ethnic fractionalization; ethnic diversity; social class; Einkommensumverteilung; Persönlichkeitspsychologie; Soziale Gruppe; Soziale Schicht; Ethnische Gruppe; Theorie